2015
DOI: 10.1007/s11356-015-5188-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to particulate air pollution and risk of myocardial infarction: a systematic review and meta-analysis

Abstract: A growing number of studies have associated short-term exposure to ambient particulate matter air pollution (PM) and risk of specific cardiovascular events, just as myocardial infarction (MI). However, the results of the recent studies were inconsistent; therefore, a systematic review and meta-analysis was performed. To synthetically quantify the association between short-term exposure to PM and risk of MI, a meta-analysis was conducted to combine the estimates of effect for a relationship between short-term e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 54 publications
6
48
1
1
Order By: Relevance
“…As we reported previously, modi able risk factors, including diabetes, hypertension, smoking and dyslipidemia totally had population attributable fraction of 36.6% and 50.2% of incident CHD among male and female Tehranian population, respectively [4]. Other reasons that might justify the high prevalence of CHD among Tehranian population are related to impact of air pollution [26,27] and stress [28], which are common in Tehran.…”
Section: Discussionmentioning
confidence: 67%
“…As we reported previously, modi able risk factors, including diabetes, hypertension, smoking and dyslipidemia totally had population attributable fraction of 36.6% and 50.2% of incident CHD among male and female Tehranian population, respectively [4]. Other reasons that might justify the high prevalence of CHD among Tehranian population are related to impact of air pollution [26,27] and stress [28], which are common in Tehran.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, there is a risk that we do not measure acute daily differences, but an effect of accumulated exposure. However, studies in the general environment have observed increased risk of CVD due to short-term variations in PM exposure, indicating that daily variations can have biological effects [35]. Furthermore, the iron foundry environment contains, in addition to PM and quartz, chemical agents from the binders used together with the sand to form the molds.…”
mentioning
confidence: 99%
“…The exact mechanisms by which short-term exposure to high levels of PM could elevate the risk of MI remains uncertain. However, several possible mechanisms for the associations have been discussed [24,44,45], including an elevated risk of inflammation [43], increased heart rate and reduced heart rate variability [46][47][48], increased blood viscosity [49,50], hypercoagulability [51], and vasoconstriction [52].…”
Section: Discussionmentioning
confidence: 99%